2022
DOI: 10.3389/fnhum.2022.1026056
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous head-movements improve sound localization in aging adults with hearing loss

Abstract: Moving the head while a sound is playing improves its localization in human listeners, in children and adults, with or without hearing problems. It remains to be ascertained if this benefit can also extend to aging adults with hearing-loss, a population in which spatial hearing difficulties are often documented and intervention solutions are scant. Here we examined performance of elderly adults (61–82 years old) with symmetrical or asymmetrical age-related hearing-loss, while they localized sounds with their h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…One notable observation of the present work is that participants who exhibited more head movements and who explored a greater spatial extent made smaller localization errors. This result is in line with the growing body of research that highlights the benefits of head movements in reducing sound localization errors (Coudert et al, 2022 ; Gaveau et al, 2022 ; Gessa et al, 2022 ; Pastore et al, 2018 ; Thurlow et al, 1967 ). Plus, it extended the observations of this benefit toward listening while immersed in common noisy contexts.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…One notable observation of the present work is that participants who exhibited more head movements and who explored a greater spatial extent made smaller localization errors. This result is in line with the growing body of research that highlights the benefits of head movements in reducing sound localization errors (Coudert et al, 2022 ; Gaveau et al, 2022 ; Gessa et al, 2022 ; Pastore et al, 2018 ; Thurlow et al, 1967 ). Plus, it extended the observations of this benefit toward listening while immersed in common noisy contexts.…”
Section: Discussionsupporting
confidence: 86%
“…This behavior is spontaneous in the sense that it is reactive to what is happening in the environment. Previous studies on the effects of the head on sound localization have shown that spontaneous head movements improve localization skills in silence (Coudert et al, 2022 ; Gaveau et al, 2022 ; Gessa et al, 2022 ; Wallach, 1948 ). This is true even when the head movements are not spontaneous but requested or guided by the experimenter (Pastore et al, 2018 ; Thurlow et al, 1967 ).…”
Section: Introductionmentioning
confidence: 99%
“…To find out which smoke alarm is chirping, one is more likely to explore the house room by room than to sit stationary and compute interaural localization cues (Groh, 2014). Finally, interaural time and localization cues are identical for a sound exactly in front and exactly behind the listener, but this ambiguity can be instantly resolved by moving the head to a new angle, which will generate very different cues for the two previously ambiguous cases (Perrett and Noble, 1997; Wightman and Kistler, 1999; Gessa et al ., 2022). These movement strategies improve SNR by moving the sensor rather than by implementing complex algorithms to process noisy data.…”
Section: Discussionmentioning
confidence: 99%
“…The spontaneous reaction of turning the head and body towards a sound source has been found to be an important factor in weighing auditory cues [ 27 , 28 ]. Studies comparing static and active listening conditions showed better spatial performance when head movements were allowed [ 18 , 22 , 29 ].…”
Section: Discussionmentioning
confidence: 99%